Peripheral Blood Lymphocyte Subsets as a Risk Predictor of Patients with Endometrioid Endometrial Cancer - Su P; An J; Yu L; Lei H; Huang L; Mao X; Sun P (Dove Medical Press, 2022)
Pingping Su,1 Jian An,1,2 Lirui Yu,1 Huifang Lei,1 Lixiang Huang,1 Xiaodan Mao,1,3 Pengming Sun1,3 1Department of Gynecology, Laboratory of Gynecologic Oncology, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian, 350001, People's Republic of China; 2Department of Gynecology, Women and Children's Hospital, School of Medicine, Xiamen University, Xiamen, People's Republic of China; 3Fujian Key Laboratory of Women and Children's Critical Diseases Research, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian, 350001, People's Republic of ChinaCorrespondence: Pengming Sun; Xiaodan Mao, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, 350001, People's Republic of China, Tel +86-591-87558732, Fax +86-591-87551247, Email fmsun1975@fjmu.edu.cn; maodan1985@yeah.netPurpose: This study aimed to explore lymphocyte subsets for the personalized prediction of endometrioid endometrial cancer (EEC) risk and evaluated the correlation between immune cells and International Federation of Gynecology and Obstetrics (FIGO) staging in patients with EEC.Patients and Methods: A case-control study was conducted to analyze the clinical data of 421 patients admitted to Fujian Maternity and Child Health Hospital from October 2017 to December 2021. t-tests or Mann-Whitney U-tests were used to analyze the percentages and absolute counts of peripheral blood lymphocyte subsets in patients with EEC and patients without cancer. The independent risk factors for ECC and FIGO stage were analyzed via multivariate binary logistic regression. The receiver operating characteristic curve was calculated to evaluate the prediction efficacy of risk factors on ECC.Results: The CD4+ T% in the 121 patients with EEC was lower than in the 300 patients without cancer (P = 0.013). The absolute counts of peripheral CD4+ T (P = 0.002) and T cells (P = 0.007) in 37 patients with EEC were lower than in 51 patients without cancer. Multivariate binary logistic regression analysis showed that CD4+ T% and natural killer cell (NK)% were independent risk factors for FIGO staging in patients with EEC. NK% was significantly higher in patients with advanced stage (FIGO III and IV) than those with early EEC (FIGO I and II) (P = 0.004). To determine the early and advance FIGO stage of EEC, the cutoff value of NK% was calculated as 19.94%.Conclusion: With the decrease of CD4+ T counts, the immune status of patients with EEC is impaired. NK cells may help in the evaluation of the prognosis of patients with EEC and are likely to be an independent risk factor for FIGO staging in patients with EEC.Keywords: CD4+ T lymphocyte, NK cells, endometrioid endometrial cancer, lymphocyte subsets, immune